2012
DOI: 10.1056/nejmoa1103151
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy Results of a Trial of a Herpes Simplex Vaccine

Abstract: Background Two previous studies of a herpes simplex virus type 2 (HSV-2) subunit vaccine containing glycoprotein D in HSV-discordant couples revealed 73% and 74% efficacy against genital disease in women who were negative for both HSV type 1 (HSV-1) and HSV-2 antibodies. Efficacy was not observed in men or HSV-1 seropositive women. Methods We conducted a randomized, double-blind efficacy field trial involving 8323 women 18 to 30 years of age who were negative for antibodies to HSV-1 and HSV-2. At months 0, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
472
4
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(494 citation statements)
references
References 19 publications
12
472
4
6
Order By: Relevance
“…A HSV subunit vaccine, HerpeVac, is a prophylactic vaccine and has the most intensive clinical study. In a study on HSV-1-and HSV-2-seronegative women, it has been found that the vaccine provides 58% protection against HSV-1; however, it has no protective efect against HSV-2 [79]. Clinical phase II studies of four prospective vaccines with therapeutic indications still continue today.…”
Section: Protection From Transmissionmentioning
confidence: 99%
“…A HSV subunit vaccine, HerpeVac, is a prophylactic vaccine and has the most intensive clinical study. In a study on HSV-1-and HSV-2-seronegative women, it has been found that the vaccine provides 58% protection against HSV-1; however, it has no protective efect against HSV-2 [79]. Clinical phase II studies of four prospective vaccines with therapeutic indications still continue today.…”
Section: Protection From Transmissionmentioning
confidence: 99%
“…Although several trials have been promising, there remain barriers to both the development of a vaccine and its implementation. [42][43][44][45][46][47] The chief limitation to this analysis was our reliance on ICD codes, which are subject to misclassification and provide no information on the characteristics of the infection, such as the infecting viral type. Some researchers have used broader ICD-9 coding and included probable cases of HSV on the basis of signs and symptoms suggestive of herpes infection.…”
Section: Figurementioning
confidence: 99%
“…Over the last 15 years there have been several failures in late stage vaccine and immunotherapeutic development programs, against viral, bacterial, parasitic, and neoplastic diseases, collectively costing $billions and decades in development [2][3][4][5]. These failures and limitations are due in large part to the lack of understanding of the human immune system, the limitations of animal models to accurately predict immune responses to vaccines in humans, and reliance on empiric strategies for vaccine development that are unlikely to be effective in the future.…”
Section: Editorialmentioning
confidence: 99%